Legalitas Sertifikasi Halal Produk Makanan Dan Minuman Impor - Evelyna, Riska Marella; Tarmidzi; Mubarok (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study examines the legality of halal certification for imported food and beverage products in Indonesia based on prevailing positive law and the mandatory procedures that must be followed by producers or importers before distributing their products in Indonesia. Halal certification serves not only as a form of legal protection for Muslim consumers but also as a mandate of Law Number 33 of 2014 concerning Halal Product Assurance. Imported products entering Indonesia must undergo a registration process and comply with import regulations, including meeting halal standards. However, in practice, the halal certification process for imported products often encounters challenges, particularly when the country of origin does not have a mutual recognition agreement on halal certification with Indonesia. This research uses a normative juridical method with a qualitative approach, analyzing laws, legal literature, and relevant policies issued by the Halal Product Assurance Organizing Agency (BPJPH). The findings indicate that legal recognition of halal certificates for imported products in Indonesia requires international cooperation in the field of halal assurance. The case of imported marshmallows containing non-halal ingredients circulating in the market highlights the lack of coordination and weak supervision by BPJPH and the Food and Drug Supervisory Agency (BPOM). This study is analyzed using the theory of legal certainty, which is closely related to consumer protection.